A complex mutant of TEM-1 beta-lactamase with mutations encountered in both IRT-4 and extended-spectrum TEM-15, produced by an Escherichia coli clinical isolate. - Sirot, D (1997)
Escherichia coli GR102 was isolated from feces of a leukemic patient. It expressed different levels of resistance to amoxicillin or ticarcillin plus clavulanate and to the various cephalosporins tested. The double-disk synergy test was weakly positive. Production of a beta-lactamase with a pI of 5.6 was transferred to E. coli HB101 by conjugation. The nucleotide sequence was determined by direct sequencing of the amplification products obtained by PCR performed with TEM gene primers. This enzyme differed from TEM-1 (blaT-1B gene) by four amino acid substitutions: Met-->Leu-69, Glu-->Lys-104, Gly-->Ser-238 and Asn-->Asp-276. The amino acid susbstitutions Leu-69 and Asp-276 are known to be responsible for inhibitor resistance of the IRT-4 mutant, as are Lys-104 and Ser-238 substitutions for hydrolytic activity of the extended-spectrum beta-lactamases TEM-15, TEM-4, and TEM-3. These combined mutations led to a mutant enzyme which conferred a level of resistance to coamoxiclav (MIC, 64 microg/ml) much lower than that conferred by IRT-4 (MIC, 2,048 microg/ml) but higher than that conferred by TEM-15 or TEM-1 (MIC, 16 microg/ml). In addition, the MIC of ceftazidime for E. coli transconjugant GR202 (1 microg/ml) was lower than that for E. coli TEM-15 (16 microg/ml) and higher than that for E. coli IRT-4 or TEM-1 (0.06 microg/ml). The MICs observed for this TEM-type enzyme were related to the kinetic constants Km and k(cat) and the 50% inhibitory concentration, which were intermediate between those observed for IRT-4 and TEM-15. In conclusion, this new type of complex mutant derived from TEM-1 (CMT-1) is able to confer resistance at a very low level to inhibitors and at a low level to extended-spectrum cephalosporins. CMT-1 received the designation TEM-50.